OMA DM v1.x compliant lightweight device management for constrained M2M devices. Issue 5 (10th June 2013) - Chu, Nhon; Raouf, Djelal; Corlay, Bruno; Ammari, Mohamed; Gligoric, Nenad; Krco, Srdjan; Ognjanovic, Nemanja; Obradovic, Aleksandar
ABSTRACT: This paper presents Exalted Lightweight For Open Mobile Alliance Device Management (OMA DM) v1.x, an alternative lightweight solution that is fully compatible with the current OMA DM protocol and with all existing OMA Management Objects. This solution aims to enable operators and service providers to leverage their existing OMA DM servers to continue supporting current OMA DM enabled mobile devices and to incrementally support new constrained machine to machine devices through an added proxy server. Exalted Lightweight For Open Mobile Alliance Device Management v1.x reduces the size of OMA DM messages by 89% while optimizing the processing performance and resource consumption. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Exalted Lightweight for Open Mobile Alliance Device Management (ELFOMA) is an alternative lightweight solution, fully compatible with OMA‐DM v1.x protocol and with all existing OMA Management Objects. This solution enables operators and service providers to reuse their existing OMA‐DM servers to incrementally support new constrained machine to machine devices through an added proxy server. As compared with OMA‐DM v1.x, ELFOMA payloads are nine times smaller. They are 3.3 times faster, less CPU demanding and 22.7 times less memory demanding to parse.